Practices and challenges in the care provided to hospitalized patients with wounds in an Emergency Care Unit (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To understand the care provided by nurses to patients with wounds who, while hospitalized in an Emergency Care Unit (UPA), await transfer to a referral hospital. Methods: This was a qualitative, exploratory, and descriptive study conducted in a virtual environment between February and March 2025 with nurses working in a UPA. Data collection was carried out through semi-structured interviews, and data analysis was performed using the Collective Subject Discourse method. Results: Thirteen nurses participated in the study, most of whom were female, with a mean age of 41 years, 15.9 years of professional experience, and 6 years of experience in the sector. Care provided to patients with wounds hospitalized in the UPA was characterized as a complex and challenging phenomenon influenced by multiple factors — overcrowding, prolonged patient stays, increased demands, nurses’ workload burden, provision of care without adequate supervision, gaps in professional training, and noncompliance with current legislation — all of which directly compromise the quality and safety of the care provided. Conclusion: The prolonged stay of patients in UPAs changes the care profile and poses challenges to nursing care for individuals with hard-to-heal wounds, within a context of work overload and structural limitations.